Impact of Spirulina platensis Extract as an Immunostimulant on the Histopathological Intestinal of Tilapia Fish (Oreochromis niloticus) Infected with Aeromonas salmonicida - Ramadhan, Maharani Kartika; Kurniasih; Untari, Tri; Fadholly, Amaq (Jurnal Veteriner dan Biomedis, 2025)
Furunculosis in fish results in financial detriment to freshwater aquaculture in Indonesia. Furunculosis, an infectious disease produced by Aeromonas salmonicida, presents a considerable risk to the large-scale farming of both salmonid and non-salmonid species in freshwater environments. This study sought to evaluate the impact of Spirulina platensis extract on the histopatological intestinal health of tilapia infected with Aeromonas salmonicida. Thirty tilapia, each around 10 cm in length, were distributed into five groups. Negative control (P0-) without immersion in Spirulina platensis extract and free from Aeromonas salmonicida infection. Positive control (P0 +) not immersed in Spirulina platensis extract, infected with Aeromonas salmonicida. Tilapia subjected to doses of 400 mg/L (P1), 600 mg/L (P2), and 800 mg/L (P3) The extraction of Spirulina platensis occurred for three hours on the seventh day (first immersion) and the fourteenth day (second immersion), followed by an evaluation of Aeromonas salmonicida infection on the twenty-first day. A necropsy of the fish was performed on day 28. Histopathological analysis revealed that Spirulina platensis extract reduced intestinal villous erosion and inflammatory cell density in the intestines of tilapia. Immunohistochemical staining demonstrated a decrease in the presence of Aeromonas salmonicida within intestinal tissue at a dosage of 800 mg/L. This work indicates that more research is necessary to examine the histological features of the intestines of tilapia infected with Aeromonas salmonicida with those supplemented with Spirulina platensis through feed.